: Mengeksplore Penggunaan Wattpad sebagai media di bahasa penggunaan strategi : Perspektif menulis guru dan murid - Ridwan Nafiul Faqih; Achmad Munir; Syafi’ul Anam (Journal of English Teaching, 2022)
Technology is playing an increasing role in education worldwide and is having a growing impact on the design and delivery of English language teaching. Teachers are expected to understand how to integrate technology into their teaching as well as know how to help learners make use of resources such as media and the internet to improve their learning of all four skills. As such technology offers both new challenges as well as new opportunities for both teachers and learners. This article investigates the use of Wattpad in language teaching and explores more from the perspective of teachers and students in the online classroom. It offers teachers and learners to vary the process of the teaching and learning processes by using technology-mediated teaching and learning. However, this study presents a mini research project on how the teacher of one school has used technology as a medium to teach the students in online classes recently due to Covid 19. Teachers and students should be collaborative so the process of teaching-learning able to run well. It will become a big challenge for the teacher to engage the students during the teaching process.